Digital Burnout as a Psychological Risk Factor for Loneliness in Generation Z: The Mediating Function of Self-Esteem - Mira Wahyu Kusumawati; Wenny Nugrahati Carsita; Muhammad Ichsan Basir; Elok Faradisa; Amin Aji Budiman (Viva Medika, 2026)
Background: Adolescents aged 15–17 years, often classified as Generation Z, are considered vulnerable to mental health problems because they are in a developmental transition from childhood to adulthood. Gen Z typically has high social media use, which may reduce opportunities for direct face-to-face interaction. Objective: This study aimed to examine the association between digital burnout and loneliness, with self-esteem as a potential mediator. Methods: This study employed a path analysis design. The study was conducted at SMAN 1 Sliyeg, Indramayu Regency, Indonesia. Participants were selected using purposive sampling with the following inclusion criteria: students aged 15–18 years, not currently using psychotropic medication, willing to participate, and able to read and write. Data were collected using a demographic questionnaire, the UCLA Loneliness Scale, and the Rosenberg Self-Esteem Scale (RSES). Results: Path analysis indicated that digital burnout significantly contributed to higher loneliness, while self-esteem showed a significant protective association with lower loneliness among Gen Z adolescents (p < 0.05). Conclusion: Digital burnout may influence loneliness directly; however, the mediating role of self-esteem requires further confirmation based on the full mediation pathway.